Construction of hypermedia for prevention of bloodstream infection - Isabel Cussi Brasileiro Dias; Eliane de Fátima Almeida Lima; Mirian Fioresi; Dirceu Carrara; Izabella Soares de Oliveira; Candida Caniçali Primo (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To describe the process of construction and assessment of the content of a Virtual Learning Object on preventing bloodstream infections associated with infusion therapy. Method: Methodological study carried out in three stages: elaborating the technical, scientific content; assessing theoretical content; and constructing the Virtual Learning Object. Results: We produced the theoretical content of the Virtual Learning Object. Such content obtained an 85% agreement in assessment, which was adequate. The final product comprised 39 content screens, which integrate the main recommendations and contain images, hypertexts, videos, case studies, and quiz, through an exclusive platform. Final Considerations: This study made it possible to portray the method for constructing and assessing the content of a Virtual Learning Object, enabling am easy application to health professionals, aiming at guiding them to quality care.